‘Her lovely presence ever near me lives’: A Brief Encounter from the Archives with May Alcott Nieriker - Azelina Flint (Janeway JS, 2018)
This article is a brief account of the professional and married life of painter, May Alcott Nieriker, sister of the author, Louisa May Alcott, who wrote Little Women (1868). I outline the theoretical importance of the current ‘archival turn’ in enabling the recovery of lesser-known female artists, and consider how scholarly bias has obscured the prolific and unpublished life-writings of Louisa May Alcott’s female relatives. The article provides a short account of how I became interested in May’s life, while conducting research for my PhD thesis on her sister at the Houghton Library, Harvard. It highlights the events and episodes of her life that stood out to me in her unpublished papers. From these materials, I provide an imagined projection of her personality, as there is yet to be a full-length biography written on her. I discuss her studies at Master Krug’s atelier in Paris and her rebellious act of painting a semi-nude African model in the classroom, while speaking out against racial prejudice. I emphasise her independence in coordinating her studies and travel, as well as her critical responses to the American art scene and Concord literati. The relationship with her mother, Abigail, is highlighted as a key influence on her life. May’s marriage to Ernest Nieriker is discussed in light of the negative reception she received for moderating her independent lifestyle, as well as the unpopularity of her husband with some Alcott-family biographers. The correspondence of May and the Nieriker family reveals the deep love between May and Ernest. Biographers are divided over the cause of May’s death, and this is discussed in light of the Nieriker correspondence. I conclude by providing a short analysis of May’s character, in order to show that she is a figure who deserves more attention within the field of nineteenth-century women’s history.